Model Pendidikan Spiritual dalam Mengembangkan Karakter Anak - Ahmad Shofiyuddin (Darajat: Jurnal Pendidikan Agama Islam, 2020)
This article aims to discuss the Spiritual Education Model in developing the Character of Children. This research method is a library research (Research Library), researchers conducted a series of activities relating to the method of collecting library data, reading and recording and processing research materials. Therefore the author collects data from the Qur'an and then examines books or other sources of reading that have relevance to this paper that is about character education for children (material review and methods). Literature research results show that: (1) the concept of Spiritual education contained in Al-Qur'an letter Luqman verses 12-19 is monotheism education, sharia education, and moral education, (2) monotheism education in the form of prohibitions for children so as not to shirk to Allah, Shari'ah Education; prayer commands to children, Moral Education includes; Birrul Walidain's command / service to both parents, prohibition to behave arrogantly, patiently, and have good words